Investigation of Machine Tool Developed Settings Influence on Productivity and Quality of Simultaneous Double-Sided Lens Processing - A. S. Kozeruk; Y. L. Malpica; A. A. Sukhotzkiy; M. I. Filonova; V. O. Kuznechik (Наука и техника)
The paper presents methodology for determining rational modes of abrasive processing for high-precision lenses while using a method of free lapping at finishing operations. Analytical expressions have been obtained to determine coordinates of reference points on a spherical surface which are necessary for mathematical modeling of its processing at pivotal machines. The paper contains results of a theoretical qualitative evaluation of high-precision operating lens surfaces formation in case of various combinations of setting parameters for technological equipment. In this case the most rational and unfavorable modes of processing have been identified. In particular, the last case presupposes shaping by changing rotational frequencies of an input link in an executive mechanism of the machine tool w2and the lens wл. An indicative feature is that a poor quality of processing has been obtained over the entire range of variation interval w2 at maximum value wл, and especially in the case when these frequencies are equal. It has been determined that the highest accuracy of processing is achieved with maximum amplitude of an oscillating tool motion, its diameter and frequency of part rotation and minimum rotational speed of the input link in the executive machine-tool mechanism. As such values of these setting parameters lead to an increased removal of an allowance in the marginal zone of a work-piece, then while processing a convex lens surface, its radius of curvature in each previous operation should be larger than a radius of curvature which is to be obtained in the process of subsequent operations. The inverse regularity of curvature radius values must be observed for a concave surface. The most advantageous values of the machine-tool setting parameters with various combinations have been proposed with the purpose to eliminate errors in the form of common as “knoll” and “hole” with due account of processing productivity and accuracy. The paper describes an influence of machine tool spindle wavering value on the processing accuracy of lenses having a wide range of diameters.